Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider each $X_i \sim N(0,1)$. Then the random variable $Y=\sum_{i=1}^n X_i^2$ is a $\chi^2$ distribution with $n$ degree of freedom. Is there any probability distribution about a weighted sum of the square of standard normal random variables $Z=\sum_{i=1}^n w_i X_i^2$?

share|cite|improve this question
up vote 2 down vote accepted

Distributions of norm squared of multi-normal distribution had been extensively studied in radio-communication theory. See paper of S.O. Rice, "Distribution of Quadratic Forms in Normal Random Variables".

It is quite easy to find the characteristic function of $Z$, since $$ \mathbb{E} \left( \mathrm{e}^{i t X_i^2} \right) = \frac{1}{\sqrt{1-2 i t}} $$ Therefore $$ \mathbb{E} \left( \mathrm{e}^{i t Z} \right) = \left( \prod_{i=1}^n 1-2 i t w_i \right)^{-1/2} $$ Inversion in closed form is possible only in special cases.

share|cite|improve this answer
Thank you for the quick answer! It seems that the paper you mentioned is dealing with a general case where $X_i$'s are not necessarily independent. By the way, can you give me a reference on the inversion in closed form for special cases? – Endo Nov 23 '11 at 17:21
@user19736 When all $w_i$ are equal, it is a rescaled $\chi^2)n$. If $n$ is even, and $Z=\sum_{s=1}^{2m} w_s^2(X_{2m-1}^2+X_{2m}^2)$. Then $Z$ follows hypoexponential distribution, being the sum of exponentials. – Sasha Nov 23 '11 at 17:40
I don't fully understand your formulation of hypoexponential distribution. So, do we have only two random variables $X_{2m-1}$ and $X_{2m}$ both from $N(0,1)$? Then I'm not sure why you use the subscript $2m-1$ and $2m$ in $X$. – Endo Nov 23 '11 at 19:41
@user19736 I am sorry. I mistyped indexes.I intended $Z = \sum_{s=1}^m w_s( X_{2s-1}^2 + X_{2s}^2 )$. – Sasha Nov 23 '11 at 19:52
I still don't understand your formulation $Z=\sum_{s=1}^m w_s (X_{2s-1}^2 + X_{2s}^2)$. We can regard $Y_s = X_{2s-1}^2 + X_{2s}^2\sim Exp(1/2)$ since $X_{2s-1}^2 + X_{2s}^2$ has a $\chi^2$ distribution of 2 degree of freedom, which equals to an exponential distribution with $\lambda=1/2$. So your formulation can be written as $Z=\sum_{s=1}^m w_s Y_s$ where each $Y_s$ has the same parameter $\lambda=1/2$. Meanwhile, the hypoexpoential distribution is defined as $Z=\sum_{s=1}^m Y_s$ where each exponential random variable has its own param $\lambda_i$. Am I missing something in your argument? – Endo Nov 25 '11 at 3:27

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.